Forensically important flies (INSECTA: DIPTERA) involved in the decomposition of rabbit carcasses at a coastal area in Sarawak, Malaysia - Mohd. Allif Najmi Musa; Mohd Aiman Hakim Ahmad Sabri; Madinah Adrus (Penerbit Universiti Kebangsaan Malaysia, 2024)
Sarco-saprophagous insect plays an important role in organic matter decomposition. The biological, ecological, and behavioural specificity of the taxa are important in the renewal of the decay history of a corpse or carcass, which frequently goes back to the lethal event. This study aims to determine forensic important flies and environmental factors that influence the decomposition stage of rabbit carcasses at the coastal area in Mukah, Sarawak (Malaysian Borneo). Three carcasses of European rabbits, Oryctolagus cuniculus, were used as animal models and they were placed at coastal area at Kampung Bunut beach in Mukah, Sarawak, Malaysia. Five decomposition stages, which are fresh, bloated, active decay, advanced decay, and dry remains, were observed throughout this study. A total of 75 individuals belongs to seven species of forensically important flies were collected and identified, namely Chrysomya defixa, Ch. megacephala, Ch. rufifacies, Hemipyrellia ligurriens, Musca domestica, Synthesiomya nudiseta, and Parasarcophaga dux. The common fly species found on decomposing rabbit was Ch. megacephala. Based on observation, the intensity of sunlight is directly proportional to the environmental temperature. Meanwhile, environmental temperature is shown to inversely related to the relative humidity. High temperatures hasten the decomposition of the carcass. However, the windy conditions around the coastal area cause rapid dehydration and bodily liquefaction. Therefore, the carcasses were shriveled before all of the bodily tissues had completely decomposed. The data on dipteran composition and environmental effects on decomposition would be useful for further medico-legal cases in Mukah, Sarawak. This is one of the few studies of flies as forensically significant species in Sarawak.